French invasion in Russia in 1812 and The First World War in caricature - Kustova, Anna E. (Actual Problems of Theory and History of Art, 2012)
The work is devoted to caricatures of two war campaigns: French invasion in Russia in 1812 and The First World War (1914–1918). Caricatures can be divided into several groups of subjects: the achievements of the nation army, the escape of enemies, the theme of the folk Russian proverbs and others. Numerous images give us an opportunity to trace the ways in which different artists using lubok’s primitive manners and types of heroes created their own special individual styles. Caricatures of the period of French invasion in Russia in 1812 stood at the beginning of a whole tradition which achieved its final stage during The First World War.
Keywords: military caricature; lubok; satire on enemies; engraving; etching; chromolithography; Napoleon; French invasion in Russia in 1812; The First World War